YOUTUBE IN THE FORMATION OF RECEPTIVE SKILLS OF STUDENTS - Kambarova Liliya Ruslanovna; Faxriddinova Mubina Ozod qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
In the conditions of the modern world, there is a demand for specialists who are able to navigate the flow of information, which is presented in different forms: it can be a written text, it can be an oral statement. A future specialist must perceive oral and written texts equally well, be able to extract the necessary information from foreign language sources, and be able to critically evaluate and compare different points of view on any issue. It can be argued that universities do not pay sufficient attention to special methodological principles of teaching, such as interconnected teaching of types of speech activity.